PERAN UN WOMEN DALAM ISU KETIDAKSETARAAN GENDER DI PAKISTAN - Setyowati, Kinanti Diah Ayu; Fitriyanti, Andini Aulia; Marsingga, Prilla (Department of International Relations Universitas Satya Negara Indonesia, 2024)
In 1994, UNDP released a report on human security, which included a point on personal security. The issue of gender inequality is a threat to personal security. Pakistan is a country that continues to advocate for and work towards gender equality. Inequalities in socio-economic development and the influence of a social structure based on a feudal system led to differences in the level of gender inequality in Pakistan. The high level of gender inequality in Pakistan affects women's ability to fully enjoy their rights. Using the concepts of international organizations, human security theory, and gender equality, this research aims to examine the role of the international organization UN Women in increasing gender equality in Pakistan. Employing a qualitative method with a descriptive approach as the framework, this research found that UN Women serves as a facilitator, communicator, and motivator in advancing gender equality, promoting Sustainable Development Goal 5, and protecting women from violence and discrimination. UN Women actively plays a role in achieving gender equality in Pakistan.